(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Curcumin, contained at Turmeric (Curcumalonga), can exert many beneficial pleiotropic activities in the gastrointestinal tract. This study evaluated the antioxidant and anti-inflammatory activity of C. longa on 5-fluorouracil (5-FU)-induced oral mucositis (OM) in hamsters. Phytochemical analysis of crude C. longa extract (CLE) was performed to detect the presence of curcumin by TLC and HPLC. Golden Syrian hamsters were orally pre-treated with CLE (5, 50, or 100mg/kg). Cheek pouch samples were subjected to macroscopic and histopathological evaluation. ELISA was performed to quantify the inflammatory cytokines IL-1β and TNF-α. Superoxide dismutase (SOD), glutathione (GSH) and malondialdehyde (MDA) levels were assessed by ultraviolet-visible spectroscopy analysis. Behavior analysis was conducted by the open field test. Curcumin content in the CLE was 0.55%m/m ± 0.0161 (2.84%). The group treated with 5mg/kg CLE showed healing evidence with macroscopic absence of ulceration (p<0.05) and microscopic aspect of re-epithelialization, discrete inflammatory infiltrate and absence of edema. Treatment with 5mg/kg CLE significantly increased GSH levels, and reduced MDA levels and SOD activity (p˂0.05), and decreased IL-1β (p˂0.05) and TNF-α (p˂0.01) levels. A significant reduction in walking distance, ambulation, speed, and rearing was observed for motor activity. Curcumin reduced oxidative stress, inflammation, and motor activity in hamsters with 5-FU-induced OM.